1984
DOI: 10.1017/s004317450005880x
|View full text |Cite
|
Sign up to set email alerts
|

Mefluidide and Acifluorfen Interactions on Ivyleaf Morningglory (Ipomoea hederacea), Velvetleaf (Abutilon theophrasti), and Common Cocklebur (Xanthium pensylvanicum)

Abstract: In greenhouse studies, postemergence applications of 0.1 or 0.3 kg ai/ha mefluidide {N-[2,4-dimethyl-5-[[(trifluoromethyl)sulfonyl] amino] phenyl] acetamide} as a tank mixture with 0.3, 0.4, or 0.6 kg ai/ha acifluorfen {5-[2-chloro-4-(trifluoromethyl)phenoxy]-2-nitrobenzoic acid}, or as a pretreatment 3, 5, or 7 days prior to acifluorfen treatment, often increased injury to ivyleaf morningglory [Ipomoea hederacea(L.) Jacq. ♯3IPOHE], velvetleaf (Abutilon theophrastiMedic. ♯ ABUTH), and common cocklebur (Xanthiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Production of field crops normally involves controll ing a variety of pests which include weeds and insects. An important tool in weed control is the use of herbi cides (3,4,5,6,7,13,14). The effects of herbicides on both predator and pest insects and injury resulting from the combination of insect injury and herbicides also have been reported (1,9,10,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Production of field crops normally involves controll ing a variety of pests which include weeds and insects. An important tool in weed control is the use of herbi cides (3,4,5,6,7,13,14). The effects of herbicides on both predator and pest insects and injury resulting from the combination of insect injury and herbicides also have been reported (1,9,10,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Penetration and translocation of 14 C in ivyleaf morningglory, velvetleaf, common cocklebur, and soybean 7 days after treatment with 14 C-mefluidide or after treatment with 14 C-acifluorfen applied alone or 0, 3, 5, or 7 days following application of 0.3 kg/ha mefluidide. suppresses growth of common cocklebur (6, 11) but has little effect on ivyleaf morningglory (6). Ivyleaf morningglory, however, absorbed 9.8% more 14 C than common cocklebur.…”
Section: Resultsmentioning
confidence: 99%
“…The 3-, 5-, and 7-day mefluidide pretreatments did not alter the translocation of radiolabel. Hook and Glenn (6) reported that applying mefluidide 3 or 7 days prior to application of acifluorfen injured ivyleaf morningglory more than either herbicide alone. This increased herbicidal activity from sequential treatments with mefluidide and acifluorfen may be explained partially by increased penetration of acifluorfen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations